Effect of advanced glycation end products on nocturia or sleep disorders: A longitudinal study. Issue 2 (5th October 2021) - Konishi, Sakae; Hatakeyama, Shingo; Imai, Atsushi; Okita, Kazutaka; Kido, Koichi; Ozaki, Yusuke; Uemura, Nozomi; Iwane, Takuro; Okamoto, Teppei; Yamamoto, Hayato; Yoneyama, Takahiro; Hashimoto, Yasuhiro; et al.
Abstract: Objective: This study aimed to investigate the effect of advanced glycation end products (AGEs) on nocturia and sleep disorders in community‐dwelling adults. Materials and Methods: This longitudinal study evaluated AGEs level, sleep disorders and nocturia frequency in 447 community‐dwelling adults between May 2011 and May 2016. Sleep disorders were evaluated using the Pittsburgh Sleep Quality Index (PSQI) score. Participants were divided into two groups: AGEs‐low (≤1.80) and AGEs‐high (>1.80). The longitudinal nocturia and PSQI changes for 5 years between the AGEs‐low and AGEs‐high groups were compared. The effect of baseline oxidative stress on worsening of nocturia or PSQI score 5 years later was evaluated using multivariable logistic regression analyses. Results: There was no significant difference in PSQI score and nocturia frequency between the AGEs‐low ( n = 223) and AGEs‐high ( n = 224) groups at baseline. The PSQI score and nocturia frequency increased significantly over 5 years in both groups. However, the PSQI score increased significantly in the AGEs‐high group compared with the AGEs‐low group, although there was no difference in nocturia. Background‐adjusted multivariable analysis showed that the AGE‐high was significantly associated with PSQI score worsening, but AGE‐high was not significantly associated with nocturia worsening. Conclusions: Oxidative stress may be significantly associated with worsening sleep disorders, although oxidative stress may not significantly worsen nocturia frequency.